2021
DOI: 10.1111/jcpt.13389
|View full text |Cite
|
Sign up to set email alerts
|

Safety of dexmedetomidine for the control of agitation in critically ill traumatic brain injury patients: a descriptive study

Abstract: Background Behavioural disturbances such as agitation are common following traumatic brain injury and can interfere with treatments, cause self‐harm and delay rehabilitation. As there is a lack of evidence on the optimal approach to manage agitation in recovering TBI patients, various pharmacological agents are used including antipsychotics, anticonvulsants and sedative agents. Among sedatives, the safety and efficacy of dexmedetomidine to control agitation in traumatic brain injury patients is not well docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Recent studies have confirmed that DEX exerts its protective effects on various organ injuries ( 12 , 20 ). Based on accumulating evidence, DEX also improves neurological function and delirium in patients ( 21 ) and alleviates EBI in the TBI model and the effect of DEX is dose-dependent ( 12 , 22 , 23 ). Huang and Hao ( 22 ) report that DEX relieves early brain injury (EBI) by inhibiting inflammation and decreasing neuronal apoptosis, which may depend on the TLR4/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that DEX exerts its protective effects on various organ injuries ( 12 , 20 ). Based on accumulating evidence, DEX also improves neurological function and delirium in patients ( 21 ) and alleviates EBI in the TBI model and the effect of DEX is dose-dependent ( 12 , 22 , 23 ). Huang and Hao ( 22 ) report that DEX relieves early brain injury (EBI) by inhibiting inflammation and decreasing neuronal apoptosis, which may depend on the TLR4/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, another study demonstrated that Dex infusion in TBI patients does not worsen neurological functioning [22]. Recently, Dex was found to be associated with a reduction in paroxysmal sympathetic hyperactivity and agitation in TBI patients [23,24]. Although opposite opinions exist considering Dex's side effects of reducing blood pressure and heart rate, researchers agreed that more studies would be necessary to evaluate Dex's effects on TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…To expand the inclusion/exclusion criteria, an IRB amendment to the original protocol was requested on September 30, 2019, with the following alterations: (1) extension of the time for exposure to fentanyl/dexmedetomidine to 48 hours pre-enrollment to allow for enrollment of patients admitted overnight and on the weekends, with a plan to carefully record the prerandomization concomitant medications and account for these in any statistical analyses; (2) removal of the traumatic brain injury and pediatric cerebral performance category > 3 exclusion, while limiting participants with these clinical features to 8 participants per cohort; (3) removal of the exclusion criterion of admission for cardiac surgery; and (4) request for a single-guardian consent. Alterations (2) and (3) were based on these patient populations already receiving dexmedetomidine in clinical practice 20,21 and having rigorous systematic assessments of these agents within the trial would provide much-needed additional evidence. The Data and Safety Monitoring Board agreed with these protocol alterations, and they agreed to provide an extra safety assessment after the first five cardiac surgery participants were enrolled.…”
Section: Changes To Study Designmentioning
confidence: 99%